Do not come late to the party: initial success of nonnative species is contingent on timing of arrival of co-occurring nonnatives - Torres, Agostina (2021)
Invasions by multiple nonnative species threaten native communities worldwide. We know that interactions among nonnative species influence nonnative success. However, we know relatively less about the influence of community assembly history on the interactions within nonnative species and thereby invasion success. To investigate this, we transplanted seedlings of two highly invasive shrubs, Rosa rubiginosa (hereafter ‘rose’) and Cytisus scoparius (hereafter ‘broom’), at two different times into mesocosm communities of native and nonnative species. We conducted priority and delay treatments that consisted of the early and late arrival of the invasive shrubs, respectively. We gave full priority/delay to each invasive shrub (rose early/late arrival, broom early/late arrival) and simultaneous priority/delay (simultaneous early/late arrival). We predicted that if assembly history were important, the invasive shrubs will benefit from early-arriving and will be disadvantaged by late-arriving and that arriving before the co-invader shrub will be more beneficial than arriving before the rest of the community. We also predicted that assembly history treatments that gave an advantage to invasive shrubs will more negatively affect native species than nonnative species. We found that the invasive shrubs did not benefit by early-arrival, but they were hindered by the early-arrival of the co-invader. The rose paid a high cost for late-arrival, but the broom was only impaired when its late-arrival implied arriving after the rose. Contrary to our predictions, natives paid a lower cost than nonnatives by arriving late. In general, our mesocosm experiment showed that the success of invasive species depended more on not arriving later than other invaders than on arriving early in the community. We suggest that community assembly history modulates the sign and strength of nonnative species interactions whose consideration might improve management practices.